1997
DOI: 10.1002/(sici)1096-9861(19970818)385:1<117::aid-cne7>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of adult-type inhibitory glycine receptors in the central auditory system of rats

Abstract: Inhibitory synaptic activity is crucial for many aspects of acoustic information processing and mainly mediated by glycine and gamma-aminobutyric acid, the two principal inhibitory neurotransmitters in the auditory system. Glycine exerts its inhibitory action via binding to postsynaptic receptors existing in various isoforms. Here we have investigated the spatiotemporal distribution of adult-type, strychnine-sensitive glycine receptors (GlyRs) in the rat auditory system by using a specific antibody against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 68 publications
12
66
1
2
Order By: Relevance
“…During the first 1.5 weeks after birth, glycine receptor mRNA and protein expression increases in the cochlear nuclei (24,34). This increase parallels the presynaptic glycine receptor localization that we have observed and coincides with an increase in glycine immunoreactivity of the glycinergic MNTB neurons themselves (35).…”
Section: Discussionsupporting
confidence: 85%
“…During the first 1.5 weeks after birth, glycine receptor mRNA and protein expression increases in the cochlear nuclei (24,34). This increase parallels the presynaptic glycine receptor localization that we have observed and coincides with an increase in glycine immunoreactivity of the glycinergic MNTB neurons themselves (35).…”
Section: Discussionsupporting
confidence: 85%
“…On the level of SG neurons, a dot-like staining pattern, which is typical of glycine receptors in CNS neurons (Friauf et al 1997;Becker et al 1991), was observed for GlyR 3 (Fig. 5a, open arrows) and gephyrin protein (Fig.…”
Section: Mrna Localization Of Glycine Receptors and Gephyrin By In Simentioning
confidence: 86%
“…6c-e) and in OHCs (Fig. 6c, d, f) of the adult (>P21) rat cochlea, reminiscent of postsynaptic GlyR clusters in the cell membrane of CNS neurons (Friauf et al 1997;Becker et al 1991).…”
Section: Glyr and Gephyrinmentioning
confidence: 92%
See 1 more Smart Citation
“…This switch is synchronized with the maturation of calyceal transmission (Awatramani et al, 2003). However, anatomical studies suggest that the expression of the "adult" glycine receptor subunit (␣1) does not peak until ϳ3 weeks after birth (Friauf et al, 1997;Piechotta et al, 2001). This led us to investigate the properties of inhibition in older animals.…”
Section: Introductionmentioning
confidence: 99%